Systematization of the prevalence of Anaplasma spp. in canines and meta-analysis of A. platys and A. phagocytophilum (2023)
Objective. To estimate the general prevalence of Anaplasma spp. and the specific prevalence of A. platys and A. phagocytophilum in canines through studies published between 2000 and 2018. Materials and methods. Systematic review with 14 search strategies to ensure exhaustivity and reproducibility in the stages specified in the PRISMA guide. Quality was evaluated with STROBE. Frequencies were calculated and global and specific prevalences were estimated by country, period of study and diagnostic test employed, with 95% confidence intervals. A forest plot was made showing the individual and global prevalences A. platys and A. phagocytophilum by PCR, ELISA, and IFI, compared using a Z-Test. Results. Thirty studies with 18.472 canines were included, mostly from Brazil, the United States, and Germany. In the studies with IFI, the prevalence was 39.0% (95% CI= 37.0-41.0); with ELISA 9.3% (95% CI=8.8-9.8); and with PCR, 7.1% (95% CI= 6.4-7.8). The prevalence with PCR was statistically higher in America at an 11.9% (95% CI= 10.5-13.3) compared to Africa, at an 5.5% (95% CI= 1.2-9.7), Asia, 4.1% (95% CI= 3.1-5.1), and Europe, 3.5% (95% CI = 2.5-4.5). The prevalence of A. platys with PCR was 16.1% (95% CI= 14.2-17.9), and of A. phagocytophilum, 3.7% (95% CI= 2.8-4.6). Conclusions. The study showed a high prevalence of the infection, with a greater presence of A. platys, in a low number of publications worldwide, with highly heterogeneous results when considering countries, diagnostic techniques, and species involved. © The Author(s), Journal MVZ Cordoba 2019.